Classical Labeling of Bacterial Pathogens According to Their Lifestyle in the Host: Inconsistencies and Alternatives - Silva, Manuel T. (Frontiers in Microbiology, 2012)
An ample understanding of the complex interactions between host and pathogen will improve our ability to develop new prophylactic and therapeutic measures against infection. Precise classification of infectious agents in regards to their infective lifestyles in the host and corresponding pathogenic implications are required because clear concepts are essential to plan fruitful research. Classically, pathogenic bacteria are classified as extracellular, facultative intracellular and obligate intracellular. In our opinion, this classification is inadequate as concluded from data here discussed. For an infectious agent, when living from pathogenicity in association with its host, more relevant in microbiological terms than that ability to grow in artificial media is whether it is capable to live intracellularly, extracellularly or both in the natural setting of the host extracellular sites. To eliminate the inconsistencies associated with the classical labeling of bacterial pathogens, we propose that bacterial pathogens be labeled exclusive extracellular, dual intracellular/extracellular and exclusive intracellular based on their infective lifestyle in the host, not in the ability to grow in artificial bacteriological media.